KEWENANGAN PEMERINTAH DAERAH DALAM PENERTIBAN PENAMBANGAN PASIR TANPA IZIN DI KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU TAHUN 2012 - Remisa, Iga; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this study was to determine the local authorities in control of illegal sand mining in the district of West Rengat Indragiri Hulu in 2012 and know the enabling and inhibiting factors in controlling illegal sand mining in the District of West Rengat Indragiri Hulu in 2012. In this study, researchers used the informant research, where researchers have understood the initial information about the object of study and research informants. Informants are formal leaders and informal leaders. Formal leaders are heads of the Department of Mines and Energy, while the informal leaders are servants who understand about the problems of research and business owner of sand mining. Qualitative data analysis which is discussed problems that occurred in a government agency are about the management of sand mining permits in the district of West Rengat Indragiri Hulu .The study states that the enforcement authority in controlling sand mining include external and internal authority. The authority has not well applied internally because of the limited number of personnel and facilities to perform law enforcement. Implementation of the government's authority in regulating sand mining can be carried out externally by involving the community and community leaders. However, most people do not actively cooperate in controlling sand mining activities, due to the lack of socialization about it . Factors that constrain the application of government authority in regulating sand mining is the authority in coaching and sanctions are less effective and less fair because application of discipline and sanctions unfair, sometimes makes people feel dissatisfied with the performance of local government officials. Lack of socialization of the importance of controlling sand mining could affect regional income and preservation of the river ecosystem .Keywords : Authority , Control, Illegal Sand Mining